PENGARUH KEPEMIMPINAN ISLAM, BUDAYA ORGANISASI ISLAM TERHADAP KINERJA PERAWAT DENGAN MOTIVASI KERJA ISLAM SEBAGAI VARIABEL INTERVENING (STUDI PADA RUMAH SAKIT ISLAM MUHAMMADIYAH KABUPATEN KENDAL) - Hishna Syadiida Rahman; Fuad Mas’ud (ITB AAS INDONESIA Surakarta, 2022)
Hospitals need a strong organizational foundation to survive in the competitive healthcare industry. In this case, human resources cannot be separated because having competent, motivated and trained employees is one of the main elements of organizational success. So that company leaders must pay attention to the performance of their employees. Leadership style is a factor of success or failure of leaders in organizations. Islam believes that leadership is a mission, a responsibility not only to the members they lead, but also to Allah SWT. Islamic leadership is an activity that aims to guide, accompany and guide to the path of Allah's blessings. This study uses primary data and secondary data in the form of information from published journals, websites or other media. The research sample includes employees of the Islamic Hospital of Muhammadiyah Kendal who have worked for 2. The technical analysis in this study was carried out using descriptive analysis and Structural Equatioan Modeling or SEM (Structural Equatioan Modeling) then tested the hypothesis. The results of hypothesis testing state that Islamic leadership has no effect on nurse performance, Islamic organizational culture has a positive effect on nurse performance, Islamic leadership has a positive effect on Islamic organizational culture, Islamic leadership has a positive effect on Islamic work motivation, Islamic organizational culture has a positive effect on Islamic work motivation. and Islamic work motivation has a positive effect on the performance of nurses. Based on the results of the Sobel Test, Islamic work motivation mediates the influence of Islamic leadership on nurse performance, but Islamic organizational culture does not mediate the influence of Islamic leadership on nurse performance. Islamic work motivation mediates the influence of Islamic organizational culture on nurse performance while Islamic organizational culture mediates the influence of Islamic leadership on Islamic work motivation.